Sharia-Compliant Digital Transactions in Islamic Boarding Schools: A Legal and Accounting Framework for Smart Contract Implementation - Anas Alhifni; Biyanti Ahwarumi; Martin Roestamy; Warizal Warizal (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Motivated by the need for greater efficiency and transparency in financial management, the research aims to explore how smart contracts can enhance operational practices while adhering to Islamic principles. This study examines the potential of blockchain-based smart contracts to facilitate Sharia-compliant digital transactions in Islamic boarding schools. A qualitative multiple-case study approach was employed, involving in-depth interviews with school leaders, business managers, and financial administrators from three major Islamic boarding schools, supported by analysis of financial records, transactional agreements, and regulatory documents. Findings indicate that smart contracts can significantly improve financial operations, particularly in managing business partnerships, charitable fund distribution, and educational fee structures. However, successful implementation requires addressing legal recognition of blockchain agreements, establishing accounting standards aligned with AAOIFI guidelines, and ensuring robust Sharia supervision consistent with National Sharia Council-Indonesian Ulema Council directives. The study also highlights variations in digital readiness across schools, emphasizing the need for a phased, context-sensitive adoption strategy. An integrated framework and readiness-based roadmap are proposed, offering a practical pathway for compliant and efficient digital financial management. This research contributes a novel conceptual framework bridging blockchain innovation and Islamic commercial jurisprudence, advancing the integration of Islamic fintech in traditional educational institutions.